2001
DOI: 10.1139/x01-100
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in growth of Pinus palustris and Pinus elliottii along a hydrological gradient in central Florida

Abstract: Forest species composition in Florida is sensitive to changes in hydrology that accompany small shifts in elevation. In this study, we use dendrochronological techniques to determine how the growth of Pinus elliottii var. elliottii Engelm. (slash pine) and Pinus palustris Mill. (longleaf pine) along a hydrologic gradient from mesic flatwoods to xeric sandhills responds to fluctuations in climate (temperature, precipitation, river flow, and Palmer drought severity index). Interspecies and intraspecies compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 13 publications
1
37
2
Order By: Relevance
“…Tree-ring analysis in Florida has primarily been limited to species located in central-northern regions of the state (Foster and Brooks 2001;Brooks 2002, 2003;Henderson and GrissinoMayer 2009). The majority of tree species in south Florida fail to produce annual rings (Tomlinson and Craighead 1972), yet our research demonstrates that slash pine is a species of dendrochronological value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tree-ring analysis in Florida has primarily been limited to species located in central-northern regions of the state (Foster and Brooks 2001;Brooks 2002, 2003;Henderson and GrissinoMayer 2009). The majority of tree species in south Florida fail to produce annual rings (Tomlinson and Craighead 1972), yet our research demonstrates that slash pine is a species of dendrochronological value.…”
Section: Discussionmentioning
confidence: 99%
“…This period was selected because conditions during the previous-and current-year growing season can affect the amount of carbon fixed and allocated to tree growth (GrissinoMayer and Butler 1993; Foster and Brooks 2001). Response-function and correlation coefficients were produced using the program DEN-DROCLIM2002, which uses bootstrapping to yield more accurate confidence levels (Biondi 1997;Biondi and Waikul 2004).…”
Section: Response Function and Correlation Analysismentioning
confidence: 99%
“…This relationship indicates that too little precipitation during the spring dry season is a limiting factor of photosynthesis and thus growth, even though the water table is generally less than 3 m below the surface during this time. Also working with peninsular Florida Pinus elliottii populations, Foster and Brooks [14] quantified the tree-ring growth correlation with precipitation. They found that dry season precipitation positively affected growth for pines growing in xeric areas, as has been shown for many southern yellow pines [19,20,37,46].…”
Section: Discussionmentioning
confidence: 99%
“…A study of loblolly pine across its range indicates its radial growth is limited by cool January and February temperatures at its NLRM in eastern Maryland and February temperatures and as it approaches its NLRM in Arkansas (Cook et al 1998). Other southern yellow pines have been studied in other portions of their range including loblolly pine (Friend and Hafley 1989;Grissino-Mayer et al 1989;Travis and Meentemeyer 1991), shortleaf pine (Friend and Hafley 1989;Travis and Meentemeyer 1991;Grissino-Mayer and Butler 1993), slash pine (Foster and Brooks 2001;Ford and Brooks 2003), and longleaf pine (Lodewick 1930;Coile 1936;Schumacher and Day 1939;Meldahl et al 1999;Devall et al 1991;Zahner 1989;Foster and Brooks 2001;Henderson and Grissino-Mayer 2009). The effects of climate on growth of the other southern yellow pines, longleaf pine (Pinus palustris P.…”
Section: Introductionmentioning
confidence: 99%